IMPACT OF BUSERELIN ACETATE ADMINISTRATION AT ESTRUS OR DURING LUTEAL PHASE ON PLASMA PROGESTERONE IN DAIRY CATTLE REARED UNDER TEMPERATE CLIMATE - JASWAL, R S; THAKUR, TARUN; SINGH, MADHUMEET; GHUMAN, S P S (The Indian Journal of Animal Reproduction, 2016)
Crossbred dairy cattle were administered (i.m.) 0.021 mg buserelin acetate, a GnRH analogue, on day of estrus (d0, n=8), or day 5 (n=8) or day 12 (n=10) post estrus, and a non-treatment group was kept as control (n=10). Plasma progesterone was estimated on day 0, 7 and 14 post estrus. Neither of the treatment had an impact on plasma progesterone as the values were similar on day 7 and 14 post estrus between treatment as well as control groups